A microfluidic biochip for locally confined stimulation of cells within an epithelial monolayer. Issue 14 (19th February 2018) - Thuenauer, Roland; Nicklaus, Simon; Frensch, Marco; Troendle, Kevin; Madl, Josef; Römer, Winfried
Abstract : We developed a microfluidic biochip that enables one to locally change the basolateral microenvironment of epithelial cells within a polarised monolayer. Abstract : A key factor determining the fate of individual cells within an epithelium is the unique microenvironment that surrounds each cell. It regulates location-dependent differentiation into specific cellular sub-types, but, on the other hand, a disturbed microenvironment can promote malignant transformation of epithelial cells leading to cancer formation. Here, we present a tool based on a microfluidic biochip that enables novel research approaches by providing a means to control the basolateral microenvironment of a confined number of neighbouring cells within an epithelial monolayer. Through isolated single pores in a thin membrane carrying the epithelial cell layer only cells above the pores are stimulated by solutes. The very thin design of the biochip (<75 μm) enabled us to apply a high-resolution inverted confocal fluorescence microscope to show by live cell imaging that such a manipulation of the microenvironment remained locally restricted to cells located above the pores. In addition, the biochip allows access for the force probe of an atomic force microscope (AFM) from the apical side to determine the topography and mechanical properties of individual cells, which we demonstrated by combined AFM and fluorescence microscopy imaging experiments. Taken together, the presented microfluidic biochip is a powerful tool that will enable studying the initial steps of malignant transformation of epithelial cells by directly manipulating their microenvironment and by real-time monitoring of affected cells with fluorescence microscopy and AFM.